High-Frequency and Low-Power Output Stages Based on FGMOS Flipped Voltage Follower. (10th February 2013) - Gupta, Maneesha; Singh, Urvashi; Srivastava, Richa
Abstract : Two new high-performance output stages are proposed. These output stages are basically designed by using a flipped voltage follower (FVF). The proposed low-power and low-voltage output stages have utilized the advantages of the FGMOS technology. They are characterized by low-power dissipation, reduced power supply requirement, and larger bandwidth. By using FGMOS-based FVF in place of conventional FVF, the linearity of the output stages has been highly improved. The small-signal analysis of FGMOS-based FVF is done to show the bandwidth enhancement of conventional FVF. The circuits are simulated to demonstrate the effectiveness using SPICE, in TSMC 0.25-micron CMOS device models. The simulation results show that the power supply requirement of the proposed output stages is highly reduced and bandwidths are extremely higher than the conventional circuits.